ANALISA PERENCANAAN PERKERASAN KAKU (RIGID PAVEMENT) APRON BANDAR UDARA SULTAN THAHA SYAIFUDDIN JAMBI - Huzeirien Huzeirien; M Eri Dahlan (Jurnal Civronlit Unbari, 2018)
The function of the Airport is like a terminal which in this case serves passenger aircraft as a stop, departure, or just an airplane stopover. at the airport there are various kinds of series of activities related to aircraft, such as transporting / dropping passengers and goods, conducting refueling, aircraft maintenance, aircraft damage repair, and so forth. The apron is part of the airport which is the area used in accommodating the aircraft to load and disassemble or degrade passengers and freight, park, and refuel. Pavement is the main structure in apron construction. This means that the apron is required to be able to accept and bear the aircraft load and traffic on it is planned properly. This study aims to calculate the rigid apron pavement construction designed so as to obtain pavement with carrying capacity capable of serving air traffic in accordance with the aircraft traffic plan.Keywords: Airport, Apron, Rigid Pavement